Impact of calcium ions on the structural and dynamic properties of heparin oligosaccharides by computational analysis. (August 2022) - Kogut, Małgorzata M.; Danielsson, Annemarie; Ricard-Blum, Sylvie; Samsonov, Sergey A.
Abstract: Heparin (HP) belongs to glycosaminoglycans (GAGs), anionic linear polysaccharides composed of repetitive disaccharide units. They are key players in many biological processes occurring in the extracellular matrix and at the cell surface. GAGs are challenging molecules for computational research due to their high chemical heterogeneity, flexibility, periodicity, pseudosymmetry, predominantly electrostatics-driven nature of interactions with their protein partners and potential multipose binding. The molecular mechanisms underlying GAG interactions mediated by divalent ions, which are important for GAG binding to several proteins, are not well understood. The goal of this study was to characterize the binding of Ca 2+ to two HP oligosaccharides of different lengths (dp10 and dp18, dp: degree of polymerization) and their impact on HP conformational space and their dynamic behavior with the use of molecular dynamics (MD)-based approaches with two Ca 2+ parameter sets. MD data suggested that the flexibility of the monosaccharides, the glycosidic linkages and ring puckering were not affected by the presence of Ca 2+, in contrast to H-bond propensities and the calculated Rg for a fraction of the oligosaccharide populations in both dp10 and dp18. Moreover, the essential differences in the data obtained by using two Ca 2+ parameter sets were reported. Graphical Abstract: ga1 Highlights: Ca 2+ parameterization strategy is crucial for modeling of heparin-ion complexes. The presence of Ca 2+ leads to the decrease of heparin's radius of gyration. The presence of Ca 2+ strengthens heparin's intramolecular hydrogen bonds. Ca 2+ does not affect heparin's glycosidic linkages or ring puckering.